How do Czech companies report fair value measurement under IFRS 13? - Jan Dvořák (European Financial and Accounting Journal, 2017)
Although the IFRS 13 standard has been effective for more than 4 years, there is virtually no practical research on this topic. Therefore, this paper focuses on reporting of fair value measurement under IFRS 13 in the Czech Republic. Firstly, the author identifies and describes the theoretical basis of IFRS 13 with a relevant literature review of the conducted research. Subsequently, the actual empirical research is presented on a sample of companies from the Czech Republic. The author reaches a conclusion that in some cases, companies in the Czech Republic fail to report compulsory information, as required by the IFRS 13 standard. Moreover, the empirical research has revealed that the proportion of the fair value measurement within fair value hierarchy is approximately one third for each of the three levels, and it does not change over time.
Keywords: M40; 650; Fair value; IFRS 13; International accounting standards